Indonesia's Diplomacy Strategy in BRICS: Bridging National Interest and Global Political Balance - Syamsudin, Achmad (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2025)
This research aims to analyze Indonesia's diplomatic strategy in BRICS as an effort to bridge national interests with the dynamics of global political balance. Indonesia's membership in BRICS, which officially began in January 2025, is a strategic step to strengthen the country's economic, political, and geopolitical position amid the global polarization between the US and China. Economically, BRICS opens up great opportunities for Indonesia to diversify export markets for key commodities such as CPO, coal, rubber and natural gas to non-traditional partners such as India, Russia and Brazil. In addition, Indonesia also utilizes funding from the New Development Bank (NDB) to finance national strategic projects, including infrastructure and green energy transition. However, challenges remain, especially in managing the risk of economic dependence on China which dominates two-thirds of the total BRICS GDP as well as competition with other members in similar commodity sectors. Politically, BRICS membership strengthens Indonesia's position as a “bridge” between the Global South and developed countries, while promoting more inclusive global governance reforms. This research uses a descriptive-analytical approach with qualitative methods to explore Indonesia's diplomacy strategy in BRICS, focusing on economic, political, and soft power aspects. The results show that BRICS membership provides significant benefits for Indonesia, both in terms of market access and geopolitical influence, but also requires caution in maintaining balanced relations with global powers such as the US and the European Union. This research recommends strengthening negotiation capacity across sectors, optimizing the NDB for green projects, and an ASEAN-based inclusive diplomacy strategy to manage internal BRICS tensions, such as Sino-Indian rivalry. Thus, BRICS becomes a multidimensional instrument for Indonesia to strengthen economic sovereignty, political stability, and national security amid increasingly complex global fragmentation.